Erratum regarding missing Declaration of Competing Interest statements in previously published articles (2020)
Erratum regarding missing Declaration of Competing Interest statements in previously published articles. Declaration of Competing Interest statements were not included in published version of the articles that appeared in previous volumes of International Journal of Pediatrics and Adolescent Medicine. Hence, the authors of the below articles were contacted after publication to request a Declaration of Interest statement